Toll-like receptor 5- and lymphotoxin β receptor-dependent epithelial Ccl20 expression involves the same NF-κB binding site but distinct NF-κB pathways and dynamics - Sirard, Jean-Claude (2009)
Canonical and alternative NF-κB pathways depend on distinct NF-κB members and regulate expression of different gene subset in inflammatory and steady state conditions, respectively. In intestinal epithelial cells, both pathways control the transcription of the gene coding the CCL20 chemokine. Lymphotoxin β receptor (LTβR) mediates long lasting CCL20 expression whereas Toll-like receptor 5 (TLR5) signals promote inducible and transient activation. Here, we investigated whether the regulation of CCL20 expression involves different promoter sites and NF-κB molecules in response to TLR5 and LTβR stimulation. In epithelial cells, both stimulation required the same promoter regions, especially the NF-κB binding site but involved different NF-κB isoforms: p65/p50 and p52/RelB, for TLR5 and LTβR-dependent activation, respectively. The dynamic of activation and interaction with CCL20-specific NF-κB site correlated with gene transcription. Similar Ccl20 expression and NF-κB activation was found in the small intestine of mice stimulated with TLR5 and LTβR agonists. In summary, different NF-κB pathways modulate CCL20 transcription by operating on the same NF-κB binding site in the same cell type.